Optimal Control. - Lewis, Frank L.; Vrabie, Draguna L.; Syrmos, Vassilis L. (Hoboken : John Wiley & Sons, 2012)
A new edition of the classic text on optimal control theoryAs a superb introductory text and an indispensable reference, this new edition of Optimal Control will serve the needs of both the professional engineer and the advanced student in mechanical, electrical, and aerospace engineering. Its coverage encompasses all the fundamental topics as well as the major changes that have occurred in recent years. An abundance of computer simulations using MATLAB and relevant Toolboxes is included to give the reader the actual experience of applying the theory to real-world situations. Major topics cove.
11 Reinforcement Learning and Optimal Adaptive Control11.1 Reinforcement Learning; 11.2 Markov Decision Processes; 11.3 Policy Evaluation and Policy Improvement; 11.4 Temporal Difference Learning and Optimal Adaptive Control; 11.5 Optimal Adaptive Control for Discrete-time Systems; 11.6 Integral Reinforcement Learning for Optimal Adaptive Control of Continuous-time Systems; 11.7 Synchronous Optimal Adaptive Control for Continuous-time Systems; Appendix a Review of Matrix Algebra; A.1 Basic Definitions and Facts; A.2 Partitioned Matrices; A.3 Quadratic Forms and Definiteness.
A.4 Matrix Calculus.
Includes bibliographical references and index.
Print version record.
Keywords: Control theory; Mathematical optimization; Mathematics; Engineering; TECHNOLOGY & ENGINEERING -- Automation; TECHNOLOGY & ENGINEERING -- Robotics; Control theory; Mathematical optimization; Electronic books